2020
DOI: 10.1101/2019.12.28.19015974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Everolimus improves the efficacy of dasatinib in PDGFRα-driven glioma

Abstract: Background: Pediatric and adult high-grade glioma (HGG) frequently harbor PDGFRA alterations. We hypothesized that co-treatment with everolimus may improve the efficacy of dasatinib in PDGFRα-driven glioma through combinatorial synergism and increased tumor accumulation of dasatinib. Methods: Dose response, synergism studies, P-gp inhibition and pharmacokinetic studies were performed on in vitro and in vivo human and mouse models of HGG. Six patients with recurrent PDGFRα-driven glioma were treated w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…In contrast, their differential response to statins ranged from modest (DIPG-XIII) to substantial (DIPG-XIII-P*) ( Supplementary Figures 6E-H ). Notably, the murine cell line of P 53 P DGFRA H3 K 27M DIPG (PPK cells), which has been demonstrated to replicate the H3K27M DIPG biology 38 and was similarly established in culture as either GS or DGC, also displayed differential sensitivity to Phenformin and Pitavastatin ( Supplementary Figures 6J-K ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, their differential response to statins ranged from modest (DIPG-XIII) to substantial (DIPG-XIII-P*) ( Supplementary Figures 6E-H ). Notably, the murine cell line of P 53 P DGFRA H3 K 27M DIPG (PPK cells), which has been demonstrated to replicate the H3K27M DIPG biology 38 and was similarly established in culture as either GS or DGC, also displayed differential sensitivity to Phenformin and Pitavastatin ( Supplementary Figures 6J-K ).…”
Section: Resultsmentioning
confidence: 99%
“…IUE was performed using sterile technique on isoflurane/oxygen-anesthetized pregnant C57BL/6 or CD1 females at E13.5. Tumors were generated with lateral ventricle (forebrain) introduction of plasmids: (1) PB-CAG-DNp53-Ires-Luciferase (dominant negative T P 53), (2) PB-CAG-PdgfraD824V-Ires-eGFP ( P DGFRA D842V), and (3) PB-CAG-H3.3 K 27M-Ires-eGFP (H3K27M), and therefore referred to as “PPK” model 38 . PPK gliomaspheres were cultured in base media containing Neurobasal-A medium (1X), MEM sodium pyruvate solution (1mM), MEM Non-Essential Amino Acids (1X), L-glutamine (2 mM), Antibiotic-Antimycotic (1X), and supplemented with fresh B27, N2, heparin (2 μg/mL), EGF (20 ng/mL), FGF (20 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The experience of everolimus in this age group may be of particular importance given the reservations expressed about the ability to provide clinical doses of the drug at sufficient concentrations to elicit significant inhibition of Pg-P (52). Notably, another recent study reported the use of everolimus to improve the CNS penetration of dasatinib in PDGFRA-driven high grade gliomas in children (53). Here, the authors found an increase in both plasma (11.2 ng/mL to 31.5 ng/mL) and CSF (0.44 ng/mL to 0.91 mg/mL) dasatinib levels in two patients after one week of dasatinib monotherapy and then after two cycles of dual therapy with dasatinib and everolimus (53), and pointed to adult phase I studies of higher doses of everolimus (up to 70 mg weekly) that were well-tolerated and resulted in mean peak levels of everolimus 10-fold higher than standard regimens (54).…”
Section: Discussionmentioning
confidence: 99%
“…Growth factor signaling inhibitors: Growth factor signaling inhibitors have typically been explored in combination with additional treatments given concerns regarding the subclonal nature of relevant mutations as well as redundancy in the downstream signaling networks. PDGFRA signaling inhibition with dasatinib prolonged survival in an IUE-based H3.3K27M pHGG model, and combination with the mTOR inhibitor everolimus demonstrated synergy [ 33 ].…”
Section: Development Of Novel Therapiesmentioning
confidence: 99%